Optical Low Resolution Spectroscopic Observations of T Pyx during the Early Phase of 2011 Outburst - A. Arai; M. Isogai; M. Yamanaka; H. Akitaya; M. Uemura (Acta Polytechnica CTU Proceedings)
We report on the results of our low resolution spectroscopic observations during the 2011 outburst of the recurrent nova T Pyx. Our observations were performed from 0.19 days to 34 days after the eruption discovered by M. Linnolt. We found Wolf-Rayet like features in our spectrum during the initial rising phase on t = 0.19 d. Following spectral developments are consistent with previous works. We discuss that the early phase of T Pyx is divided into three stages, a short lived WR-like stage, He/N stage and Fe II stage.